Arbuscular mycorrhizal fungi in a wetland constructed for benzene‐, methyl tert‐butyl ether‐ and ammonia‐contaminated groundwater bioremediation. Issue 1 (31st July 2012) - Fester, Thomas
Summary Arbuscular mycorrhizal fungi (AMF), which are present in most natural environments, have demonstrated capacity to promote biodegradation of organic pollutants in the greenhouse. However, it is not certain whether AMF can spontaneously establish in phytoremediation systems constructed to decontaminate groundwater, because of the unusual conditions during the construction and operation of such systems. To assess this possibility, root samples from a wetland constructed for the phytoremediation of groundwater contaminated with benzene, methyl tert‐butyl ether and ammonia were analysed. Substantial AMF colonization was observed in plant roots sampled close to the inlet of a basin filled with fine gravel and planted with Phragmites australis. In addition, analysis of a fragment of the nuclear large ribosomal subunit, amplified by nested PCR, revealed the presence of AMF molecular operational taxonomic units closely related to Funneliformis mosseae and Rhizophagus irregularis in the samples. These findings demonstrate the capacity of generalist AMF strains to establish spontaneously, rapidly and extensively in groundwater bioremediation technical installations.